Detection of Multipath Propagation Effects in SAR-Tomography with MIMO Modes - Rommel, Tobias; Krieger, Gerhard (European Conference on Synthetic Aperture Radar (EUSAR), 2016)
This paper introduces a Multiple-Input Multiple-Output (MIMO) concept for Synthetic Aperture Radar (SAR) tomography. Basic idea is to localize multipath propagation effects with a combined transmit and receive Digital Beam Forming (DBF) technique. Major part of this paper is attended to the description of a MIMO-radar experiment, conducted for a final proof of concept. For this experiment, a ground-based MIMO-radar was placed on top of a building, while the antenna array was looking downwards to a dihedral scatterer placed on a meadow. In addition, the equivalent phase center of the target was covered with absorbing material to avoid direct reflections. By using an antenna beam configuration, where the transmit and the receive antenna beams are looking to the equivalent phase center of the dihedral scatterer, it was possible to suppress the target. In a repeated processing of the same acquired data set, where each of the antenna beams illuminates one of the two perpendicularly aligned surfaces of the dihedral scatterer, the target appeared in the range compressed data.
DLR Import::2019-04-03